Secα-cosα = Sinαtanα
Answers
Answered by
1
some properties of trigonometry used here
Attachments:
![](https://hi-static.z-dn.net/files/dfc/a67f18fa5a9f9cffa24f311306029943.jpg)
Animesh282:
galat hai
Answered by
1
Hey....!!! here is ur answer..........
__________________________
__________________________
To prove: secA - cosA = sinAtanA
------------------------_------------------------
On taking L.H.S.,
secA - cosA
(1/cosA) - cosA {we know that,secA = 1/cosA}
(1-cos²A)/cosA
sin²A/cosA {we know that,1-cos²A = sin²A}
sinA*sinA/cosA
sinAtanA {we know that,sinA/cosA= tanA}
= R.H.S.
I hope it helps u..........
THANK YOU..........!!!!!!
☺️☺️☺️☺️✌️✌️✌️
__________________________
__________________________
To prove: secA - cosA = sinAtanA
------------------------_------------------------
On taking L.H.S.,
secA - cosA
(1/cosA) - cosA {we know that,secA = 1/cosA}
(1-cos²A)/cosA
sin²A/cosA {we know that,1-cos²A = sin²A}
sinA*sinA/cosA
sinAtanA {we know that,sinA/cosA= tanA}
= R.H.S.
I hope it helps u..........
THANK YOU..........!!!!!!
☺️☺️☺️☺️✌️✌️✌️
Similar questions